A review of data analysis systems - Whitehead, G. D. (College of Aeronautics, 1965)
This review gives an appraisal of 8 Automatic Time history reocrd analysis systems. The appraisal indicates the analytical capabilities, analysis flexibility and the cost involved in performing the analysis. It is suggested that in choosing such a system for an educational institution, some analysis speed and automation should be sacrificed for computational flexibility and operational adaptability. The review does not indicate that a specific machine be considered, but rather that an analysis system be built from a number of manufacturing sources.